Left Ventricular Global Longitudinal Strain Is Associated With Cardiovascular Outcomes in Patients Who Underwent Permanent Pacemaker Implantation - Kim, Dae-Young; Lkhagvasuren, Purevjargal; Seo, Jiwon; Cho, Iksung; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2021)
Background: Patients who underwent permanent pacemaker (PM) implantation have a potential risk of left ventricular (LV) systolic dysfunction. However, assessment of LV ejection fraction (LVEF) shows a limited role in identifying subclinical LV systolic dysfunction and predicting cardiovascular (CV) outcomes. Methods: We reviewed 1,103 patients who underwent permanent PM implantation between January 2007 and December 2017. After excluding patients who did not undergo echocardiograms before or after PM implantation and those with LV ejection fraction (LVEF) <50%, significant valve dysfunction, and history of cardiac surgery before PM implantation, 300 (67±13 years, 119 men) were finally analyzed. LV mechanical function was assessed with LV global longitudinal strain (LV-GLS) using 2-dimensional speckle-tracking echocardiography. CV outcomes were defined as a composite of CV death and hospitalization for heart failure. Results: At 44±28 months after post-PM echocardiogram, 23 patients (7.7%) had experienced CV outcomes. Patients with CV outcomes were older and had more comorbidities and a lower baseline |LV-GLS| than those without CV outcomes. LV mechanical function worsened after PM implantation in patients with CV outcomes. The cut-off value of 11.2% in |LV-GLS| on post-PM echocardiogram had a better predictive value for CV outcomes (AUC; 0.784 vs 0.647, p = 0.012). CV outcome in patients with |LV-GLS|<11.2% was worse than that in those with |LV-GLS|≥11.2% (log-rank p <0.001). Multivariate Cox model revealed that reduced |LV-GLS| was independently associated with CV outcomes. Conclusions: Pacing deteriorates LV mechanical function. Impaired LV-GLS is associated with poor CV outcomes in patients who underwent PM implantation.